Secure and efficient group handover authentication protocol based on trajectory prediction in 5G-V2X - Yinghui ZHANG; Jiale QIAN; Jin CAO; Dong ZHENG (Tongxin xuebao)
Aiming at the efficiency issue of handover authentication for a large number of vehicles in the 5G-V2X scenario, a secure and efficient group handover authentication protocol based on trajectory prediction was proposed.Firstly, the effect of completing key agreement protocol in advance was achieved by predicting vehicle trajectories.Secondly, vehicles with mobility relevance were treated as the same group through user grouping algorithms, and then all vehicles within the group were batch verified using certificateless aggregation signature technology.In addition, to address the vulnerability of aggregated signature technology to DoS attacks, a binary search method was used to quickly locate malicious users and improve the efficiency of group handover authentication protocol.Finally, the security analysis of the protocol was conducted using the formal verification tool Scyther, and compared with the existing optimal protocol, the computational efficiency is improved by 30%.